2010
DOI: 10.1093/rheumatology/kep468
|View full text |Cite
|
Sign up to set email alerts
|

Urinary neutrophil gelatinase-associated lipocalin as a novel biomarker for disease activity in lupus nephritis

Abstract: uNGAL predicts renal flare in patients with a history of biopsy-proven nephritis with high sensitivity and specificity. Furthermore, uNGAL is a more sensitive and specific forecaster of renal flare in patients with a history of lupus nephritis than anti-dsDNA antibody titres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 27 publications
6
85
1
1
Order By: Relevance
“…20,21 In a cross-sectional single-cohort study using a modest sampling of patients with LN, we previously reported that serum or urine CSF-1 was elevated in patients with LN compared with those who had other noninflammatory kidney diseases and healthy controls; in that study we also found that amplified CSF-1 levels correlated with more severe clinical disease activity. 8 Another study indicated that flares were more likely in patients with persistently increased regulated upon activation normal T cell expressed and presumably secreted or M-CSF (also known as CSF-1) levels in urine after induction therapy using group survival curve analysis.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…20,21 In a cross-sectional single-cohort study using a modest sampling of patients with LN, we previously reported that serum or urine CSF-1 was elevated in patients with LN compared with those who had other noninflammatory kidney diseases and healthy controls; in that study we also found that amplified CSF-1 levels correlated with more severe clinical disease activity. 8 Another study indicated that flares were more likely in patients with persistently increased regulated upon activation normal T cell expressed and presumably secreted or M-CSF (also known as CSF-1) levels in urine after induction therapy using group survival curve analysis.…”
Section: Discussionmentioning
confidence: 62%
“…Urinary, but not serum, neutrophil gelatinase-associated lipocalin predicted renal flares in patients with LN and is reportedly a more sensitive forecaster of flares in patients with a history of LN than are dsDNA antibody titers, but its predictive value was not superior to that of C3c and C4 in patients with LN. 21,24 By comparison, our longitudinal analysis of individual patients suggests that elevated serum and urine CSF-1 levels may predict LN recurrences, and elevated serum CSF-1 may herald the onset of LN in advance of glomerular dysfunction and multiple clinical LN measures, including dsDNA. Thus, our current study indicates that monitoring serum or urine CSF-1 offers a potential individualized approach to the management of patients with LN.…”
Section: Discussionmentioning
confidence: 97%
“…Validation in large longitudinal studies that also include recently described urinary biomarkers for disease activity in childhood LN [4,[36][37][38], correlations with the activity and chronicity scores in renal biopsy, and lupus Fig. 4 High levels of complement split products in active LN.…”
Section: Discussionmentioning
confidence: 99%
“…Potential biomarkers include IL-6 (2), IL-18 (3), MCP-1 (4), VCAM-1 (5, 6), NGAL (7,8), and TWEAK (9,10). Indeed urine may be by far the best source for screening biomarkers for kidney diseases for several reasons.…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 99%
“…Given the fact that ϳ60% of lupus patients eventually develop kidney disease (1), there is an urgent need to find solutions to these challenges. In recent years, there have been several studies demonstrating association of urine biomarkers with lupus nephritis, including CSF-1 (28), ICAM-1 (6); NGAL (8) , FIG. 4.…”
Section: Urinary Angiostatin Reflects Renal Chronicity Changes In Lupmentioning
confidence: 99%